2019
DOI: 10.1085/jgp.201912434
|View full text |Cite
|
Sign up to set email alerts
|

An interaction between the III-IV linker and CTD in NaV1.5 confers regulation of inactivation by CaM and FHF

Abstract: Voltage gated sodium channel (VGSC) activation drives the action potential upstroke in cardiac myocytes, skeletal muscles, and neurons. After opening, VGSCs rapidly enter a non-conducting, inactivated state. Impaired inactivation causes persistent inward current and underlies cardiac arrhythmias. VGSC auxiliary proteins calmodulin (CaM) and fibroblast growth factor homologous factors (FHFs) bind to the channel’s C-terminal domain (CTD) and limit pathogenic persistent currents. The structural details and mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 42 publications
5
44
3
Order By: Relevance
“…We have shown that E1784K-induced increases in noninactivating current are dependent on a positive charge at position 1784, and that mutants at position 1784 can alter fast inactivation voltage dependence and rates without affecting the fraction of noninactivating current. These data, in conjunction with other recent studies on this region, confirm that the C terminus forms multiple interactions with the sodium channel inactivation machinery (Clairfeuille et al, 2019;Gade et al, 2020). We confirm that an interaction occurs between residue E1784E of the C terminus and the DIII-DIV linker at sites K1492 and K1493.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…We have shown that E1784K-induced increases in noninactivating current are dependent on a positive charge at position 1784, and that mutants at position 1784 can alter fast inactivation voltage dependence and rates without affecting the fraction of noninactivating current. These data, in conjunction with other recent studies on this region, confirm that the C terminus forms multiple interactions with the sodium channel inactivation machinery (Clairfeuille et al, 2019;Gade et al, 2020). We confirm that an interaction occurs between residue E1784E of the C terminus and the DIII-DIV linker at sites K1492 and K1493.…”
Section: Resultssupporting
confidence: 90%
“…1 B). Similar to previous data Deschênes et al, 2000;Gade et al, 2020;Abdelsayed et al, 2015), E1784K shows a trend toward depolarization compared with E1784E (P = 0.1554; Fig. 1 B).…”
Section: Conductancesupporting
confidence: 90%
See 2 more Smart Citations
“…By comparison with cardiomyocytes, the Na V 1.5 IQ/AA channels exhibit strong late Na + current when expressed heterologously. To determine regulatory factors that prevent late Na + current for IQ/AA mutant ch, we considered fibroblast growth factor homologous factors (FHFs), which are within the Na V 1.5 proteomic subdomain in the heart, can bind to the C-terminal domain of Na V 1.5, and have been implicated in the regulation of late Na + current ( 11 , 12 , 19 21 ). We found that FGF13, the predominant cardiac isoform in rodents ( 22 ), diminished late current of the IQ/AA mutant, suggesting that endogenous FHFs may serve to prevent late Na + current in cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%